Using information technology in mathematics education - Henderson, Norma; Tooke, D. James (New York : Haworth Press, 2001)
A collection of articles which explore the different ways information technology can be applied to mathematics education in the classroom.
"Using information technology in mathematics education has been co-published simultaneously as Computers in the schools, volume 17, numbers 1/2 2001.".
Includes bibliographical references and index.
Professional
Keywords: Mathematics -- Computer-assisted instruction; Mathematics -- Computer-assisted instruction